2015
DOI: 10.3171/2015.1.spine141041
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive resection and vertebroplasty for an osteolytic C-1 metastasis of malignant meningioma: case report

Abstract: Malignant meningiomas are a rare but aggressive subset of intracranial meningiomas leading to a very limited life expectancy. The occurrence of spinal metastases in these tumors is an even rarer event. The described patient had an intracranial malignant meningioma and developed a symptomatic osteolytic contrast-enhancing lesion in the left C-1 lateral mass suspicious for metastasis. The authors performed a minimally invasive posterior resection of the lesion with vertebroplasty of C-1. Histopathology v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been reported that prophylactic occlusion of the vertebral artery was used to avoid cement entering the vertebral artery. 20 However, this is not feasible if there are lesions in both lateral masses of the atlas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that prophylactic occlusion of the vertebral artery was used to avoid cement entering the vertebral artery. 20 However, this is not feasible if there are lesions in both lateral masses of the atlas.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that many distinct specialties and journals were represented among the studies on this list is very interesting and supports the notion that spinal tumors are best treated in a multidisciplinary and multimodal fashion. 114 Advances in genetics-based treatments, 37 radiosurgery, 17 proton-beam therapy, 2,86 immunotherapy, 18 and minimally invasive surgery, 36,38,70,81 among others, will be an important part of the future of spinal oncology. Treatments involving wild-type neurofibromatosis 2 gene insertion, oncolytic viruses, and transfer of gene-silencing ribonucleic acid have all shown promising results in vitro for meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…They allow performing traditionally open procedures, such as microdiscectomy or spinal fusion, through percutaneous and endoscopic approaches extremely minimally invasive and atraumatic for the tissues. Moreover the association of minimally invasive techniques with the operative microscope allows the surgeon to minimize the tissue damage gaining optimal results in terms of outcome [1, 2]. …”
mentioning
confidence: 99%